Roses - Meacham, Leila, 1938- (Grand Central Pub., 2010)
"Spanning the 20th century, the story of Roses takes place in a small East Texas town against the backdrop of the powerful timber and cotton industries, industries controlled by the scions of the town's founding families"--Provided by publisher.